Edukasi Penyakit Mulut dan Kuku pada Masyarakat Desa Rotnama di Kabupaten Maluku Barat Daya untuk Mencegah Penularan Penyakit pada Hewan Berkuku Belah - Inggrid Welerubun (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2024)
Foot and mouth disease (FMD) is a viral infection caused by the Genus Aphthovirus (Family Picornaviridae) that affects cloven-hoofed animals. This sickness affects the economic, social, and cultural spheres. Indonesia has been free from Foot-and-Mouth Disease since its proclamation in 1986, a status confirmed by the World Animal Health Organization in 1990. The resurgence of Foot-and-Mouth Disease (FMD) in animals in Indonesia occurred on 25 June 2022, as per the Decree of the Minister of Agriculture (Kepmentan) of the Republic of Indonesia No. 500.1/KPTS/PK/300/M/06/2022. Although Rotnama Village in Southwest Maluku Regency has not been designated as an epidemic location per the Minister of Agriculture's Decree, it is imperative to educate inhabitants about this disease to avert broader dissemination. Education is also offered to underscore that FMD is not transmissible from animals to humans. Instruction on FMD and the protocols for processing meat from FMD-infected animals is conducted via PowerPoint presentations, leaflet distribution, and poster displays. Participants exhibited considerable enthusiasm for the socialization activities, with attendance above expectations, and they also provided positive feedback regarding the events. This activity enhanced public knowledge through the participation of three individuals who accurately responded to each question posed during the interactive quiz session at the conclusion of the event. Subsequent to the outreach, residents will be informed on the proper processes for processing meat from animals afflicted with FMD, ensuring its safety for human consumption and mitigating the risk of transmission to other susceptible animals..